1939. COVID-19 vaccine immunogenicity among CD19 receptor T-cell (CAR-T) therapy. (15th December 2022) - Aleissa, Muneerah M; Little, Jessica S; Davey, Sonya; Gonzalez-Bocco, Isabel H; Looka, Andrew; Issa, Nicolas C; Hammond, Sarah P; Jacobson, Caron; Sherman, Amy C
Abstract: Background: Patients receiving CAR-T therapy may have impaired humoral responses to SARS-CoV-2 vaccinations due to their high net state of immunosuppression associated with the underlying disease, prior lines of therapy and CAR-T treatment associated hypogammaglobinemia. Comprehensive data on vaccine immunogenicity in this patient population are currently lacking. Methods: A single-center retrospective study of adults receiving CD19 CAR-T therapy for non-Hodgkin's lymphoma was conducted between 3/27/2018 – 8/31/2021. Patients received at least two doses of COVID-19 vaccinations with BNT162b2 (Pfizer, BioNTech), mRNA-1273 (Moderna), or 1 dose of Ad26.COV2.S (Janssen) and had SARS-CoV-2 anti-spike (S) levels measured at least one month after the last vaccine dose. We excluded patients who received COVID-19 monoclonal antibody therapy or immunoglobulin within 3 months of the index anti-S titer. Patients were followed from the time of the first COVID-19 vaccines through their index anti-S antibody result. Patients were censored on the first day of any additional antineoplastic therapy after disease relapse. Our primary endpoint was the percentage of patients who develop a positive anti-S response (assessed by anti-S assay cutoff of >0.8 U/mL, Roche assay). Results: Twenty-five patients met eligibility. Median age was 65 years (range 41 – 78), and majority of patients were male (72%). The number of patients with a positive antibody response was 12 (48%). Median number of vaccines received was 3. 18 patients (72%) received Pfizer vaccines, 4 patients (16%) received Moderna, 2 patients (8%) received Moderna and Pfizer, and 1 patient (4%) received Janssen and Pfizer. Median anti-S titers among patients with a positive response was 111 U/mL (range 2.44 – 12500). Two patients (8%) had COVID-19, both with negative anti-S responses. Conclusion: Our analysis shows that only 48% of patients who received CAR-T therapy developed a positive antibody response after at least two COVID-19 vaccine doses, with a low median titer among responders. This patient population is at higher risk for developing severe COVID-19 disease and likely remains vulnerable even after vaccination. Alternative approaches are needed to prevent COVID-19 and mitigate disease severity in patients undergoing CAR-T. Disclosures: Nicolas C. Issa, MD, AiCuris: Grant/Research Support|Merck: Grant/Research Support Sarah P. Hammond, MD, F2G: Advisor/Consultant|F2G: Grant/Research Support|GSK: Grant/Research Support|Scynexis: Grant/Research Support Caron Jacobson, MD, MMSc, Abintus Bio: Advisor/Consultant|Bluebird Bio: Advisor/Consultant|BMS/Celgene: Advisor/Consultant|Daiichi-Sankyo: Advisor/Consultant|Epizyme: Advisor/Consultant|ImmPACT Bio: Advisor/Consultant|Instill Bio: Advisor/Consultant|Ipsen: Advisor/Consultant|Kite/Gilead: Advisor/Consultant|Kite/Gilead: Grant/Research Support|Lonza: Advisor/Consultant|Novartis: Advisor/Consultant|Pfizer: Grant/Research Support.